Non-scanning Fluorescence Confocal Microscopy using Laser Speckle Illumination - Jiang, Shihong (2005)
Confocal scanning microscopy (CSM) is a much used and advantageous form of microscopy. Although CSM is superior to conventional microscopy in many respects, a major disadvantage is the complexity of the scanning process and the sometimes long time to perform the scan. In this thesis a novel non-scanning fluorescence confocal microscopy is investigated. The method uses a random time-varying speckle pattern to illuminate the specimen, recording a large number of independent full-field frames without the need for a scanning system. The recorded frames are then processed in a suitable way to give a confocal image. The goal of this research project is to confirm the effectiveness and practicality of speckle-illumination microscopy and to develop this proposal into a functioning microscope system. The issues to be addressed include modelling of the system performance, setting up experiments, computer control and image processing. This work makes the following contributions to knowledge: * The development of criteria for system performance evaluation * The development of methods for speckle processing, whereby the number of frames required for an image of acceptable quality can be reduced * The implementation of non-scanning fluorescence confocal microscopy based upon separate recording of the speckle patterns and the fluorescence frames, demonstrating the practicality and effectiveness of this method * The realisation of real-time image processing by optically addressed spatial light modulator, showing how this new form of optical arrangement may be used in practice The thesis is organised into three main segments. Chapters 1-2 review related work and introduce the concepts of fluorescence confocal microscopy. Chapters 3-5 discuss system modelling and present results of performance evaluation. Chapters 6-8 present experimental results based upon the separate recording scheme and the spatial light modulation scheme, draw conclusions and offer some speculative suggestions for future research.